2013
DOI: 10.1016/s0924-9338(13)75770-5
|View full text |Cite
|
Sign up to set email alerts
|

423 – The effects of portulaca oleracea L(purslane) on psychologic symptoms of schizophrenic patients

Abstract: Background:Despite the availability of an ever-expanding range of typical and atypical antipsychotics, a substantial proportion of patients with schizophrenia show a partial or total lack of response to antipsychotic mono therapy. This study was done to evaluate the effect of purslane on psychologic symptoms of schizophrenic patients.Materials and methods:This randomized clinical trial study was carried out on 60 chronic schizophrenic patients in Sina hospital Shahrekord, Iran during 2011-12. Subjects were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Of those, four studies were discarded for the following reasons: (a) non‐RCT design, (b) studies not included data of interest or not provided sufficient data for the outcomes, and (c) irrelevant for the meta‐analysis. Finally, 10 studies (Bedakhanian, Entezari, Ghanadian, Askari, & Maracy, 2017; Dehghan et al, 2016; Fakoori Jouibari, Farzanegi, & Barari, 2014; Farzanegi, 2014; Gheflati et al, 2019; Ghorbanian, Saberi, Azali Alamdari, Shokrollahi, & Mohammadi, 2019; Mohammadzadeh et al, 2016; Parvin, Farzaneh, Vardanjani, Goodarzi, & Nikfarjam, 2013; Rafiee Vardanjani et al, 2013; Zakizadeh et al, 2015) met the eligibility criteria and were included in the quantitative meta‐analysis. Four studies reported the CRP (Bedakhanian et al, 2017; Dehghan et al, 2016; Farzanegi, 2014; Parvin et al, 2013), five (Fakoori Jouibari et al, 2014; Gheflati et al, 2019; Ghorbanian et al, 2019; Rafiee Vardanjani et al, 2013; Zakizadeh et al, 2015), four (Gheflati et al, 2019; Ghorbanian et al, 2019; Mohammadzadeh et al, 2016; Zakizadeh et al, 2015), and three (Fakoori Jouibari et al, 2014; Ghorbanian et al, 2019; Mohammadzadeh et al, 2016) articles reported MDA, TAC, and SOD, respectively, as outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of those, four studies were discarded for the following reasons: (a) non‐RCT design, (b) studies not included data of interest or not provided sufficient data for the outcomes, and (c) irrelevant for the meta‐analysis. Finally, 10 studies (Bedakhanian, Entezari, Ghanadian, Askari, & Maracy, 2017; Dehghan et al, 2016; Fakoori Jouibari, Farzanegi, & Barari, 2014; Farzanegi, 2014; Gheflati et al, 2019; Ghorbanian, Saberi, Azali Alamdari, Shokrollahi, & Mohammadi, 2019; Mohammadzadeh et al, 2016; Parvin, Farzaneh, Vardanjani, Goodarzi, & Nikfarjam, 2013; Rafiee Vardanjani et al, 2013; Zakizadeh et al, 2015) met the eligibility criteria and were included in the quantitative meta‐analysis. Four studies reported the CRP (Bedakhanian et al, 2017; Dehghan et al, 2016; Farzanegi, 2014; Parvin et al, 2013), five (Fakoori Jouibari et al, 2014; Gheflati et al, 2019; Ghorbanian et al, 2019; Rafiee Vardanjani et al, 2013; Zakizadeh et al, 2015), four (Gheflati et al, 2019; Ghorbanian et al, 2019; Mohammadzadeh et al, 2016; Zakizadeh et al, 2015), and three (Fakoori Jouibari et al, 2014; Ghorbanian et al, 2019; Mohammadzadeh et al, 2016) articles reported MDA, TAC, and SOD, respectively, as outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The supplementation was based on purslane powder and extract, with daily recommended dose varying between 60 mg extract and 10 g powder. The design of all studies was parallel and the sample size ranged from 14 to 98 individuals in which the clinical conditions involved: metabolic syndrome (Bedakhanian et al, 2017), schizophrenia (Parvin et al, 2013; Rafiee Vardanjani et al, 2013), aphthous stomatitis (Mohammadzadeh et al, 2016), nonalcoholic fatty liver disease (Gheflati et al, 2019), type 2 diabetes (Dehghan et al, 2016; Fakoori Jouibari et al, 2014; Farzanegi, 2014; Zakizadeh et al, 2015), and healthy subjects with overweight or obesity (Ghorbanian et al, 2019). The mean age of participants was 42.9 years old.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations